Research on Biomass and Biochar of Reed (Phragmites australis) in U Minh Thuong National Park, Vietnam - Thai, Luom Thanh; Dang, Ngoc Thi Hong; Ngo, Thien Van; Danh, Mo; Truong, Hao Thanh; Nguyen, Bao Manh Ngoc (International Journal of Membrane Science and Technology, 2024)
Aims: Reed (Phragmites autralis) is a plant species with a seasonal reproductive cycle, it has a very high biomass in U Minh Thuong National Park. in Vietnam. To evaluate fresh and dry biomass, then made of biochar on reed plants to use biochar products provide bio-organic fertilizer raw materials for watermelon plant in agriculture. Methods: To achieve that goal several experiments were performed as (1) investtigate the biomass of fresh and dry reeds and made of biochar by using the traditional method; (2) adsorption with pig urine and chemical fertilizer (nitrogen, phosphorus and potash) to see the retention off chemical coponents dispersed into the environment in the adsorbed biochar; (3) mix biochar with inorganic mineral fertilizers and peat to from some inorganic fertilizer – biochar formulas, then consider the chemical composition of that mixture; (4) using some mix biochar fertilizer to grow watermelon with local varieties.Results: The results show that reeds can provide very high biomass to made of biochar fertilizer and reed biochar can adsorption the pig urine as ammonium, nitrate, nitrogen, phosphorus and it also adsorption inorganic as nitrogen, phosphorus and potash. So it is possible to propose the use study for planting watermelon and application treatment environment in the region polluted.Conclusions: Biomass and biochar of reed is very high, biochar can adsorb nitrogen, phosphorus and potash fertilizer; biochar can mixed peat and inorganic mineral fertilizer to planting watermelon in Mekong Delta